KEBIJAKAN LUAR NEGERI INDONESIA DALAM MENINGKATKAN KEAMANAN KESEHATAN MELALUI KERJA SAMA DENGAN REPUBLIK RAKYAT TIONGKOK TAHUN 2017-2021 - Mey Siregar; Ahmad Fuadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research analyzes the foreign policy of the Republic of Indonesia in an effort to improve its health security through cooperation in the health sector with the People's Republic of China with research limitations 2017-2021. Indonesia is a country in Southeast Asia that still has a high level of production capacity for health services, such as: raw materials for medicines, medical devices, and vaccines that are not sufficient for national needs. This research uses qualitative methods with descriptive analysis type of research. The data collection uses qualitative data collection techniques, with the types of primary data collection and secondary data collection. Meanwhile, this research uses state level analysis to understand the actions and roles of the state in determining foreign policy. This research finds that during Joko Widodo’s reign, Indonesia has a policy of foreign cooperation in the health sector which is regulated in Peraturan Menteri Kesehatan Republik Indonesia No. 64 Tahun 2015. The manifestation of this policy is the cooperation in the health sector between Indonesia and China in 2017. Through principle of free-active foreign policy with inward-looking attribute, Indonesia seeks to maintain a dynamic balance in the Southeast Asian region, and avoids the perception of the tendency to side with the power from China or from Western countries in the international political constellation. Through cooperation in the health sector with China, Indonesia manages to meet the percentage of the availability of medicines, medical devices, and vaccines of 60% originating from China as a reverberations to the cooperation between the two countries in the health sector. Keywords: Foreign Policy, Healtth Security, Inward-looking